2022
DOI: 10.3390/agriculture12020142
|View full text |Cite
|
Sign up to set email alerts
|

Liming and Phosphate Application Influence Soil Carbon and Nitrogen Mineralization Differently in Response to Temperature Regimes in Allophanic Andosols

Abstract: Andosols are characterized by high organic matter content and play a significant role in carbon storage. However, they have low phosphorus fertility because of the high phosphate-fixing capacity of active aluminum. For agricultural use of Andosols, it is necessary to ameliorate its poor phosphorus fertility by applying lime and high doses of phosphate fertilizers. The objective of the present study was to clarify how such soil amendments affect the mineralization of soil organic carbon (C) and nitrogen (N) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The results suggested that the imbalanced C:N:P stoichiometry, characteristics of agricultural soil, may lead to decoupled C, N, and P biogeochemical cycles, thereby having an adverse impact on soil C sequestration. Matsuoka-Uno et al [4] showed that the mineralization of organic matter in humus-rich Andosol is greatly enhanced by liming and phosphorus fertilization, shedding light on the importance of fertilizer management for C accumulation in agricultural land, similar to the study by Liu et al [3].…”
mentioning
confidence: 61%
“…The results suggested that the imbalanced C:N:P stoichiometry, characteristics of agricultural soil, may lead to decoupled C, N, and P biogeochemical cycles, thereby having an adverse impact on soil C sequestration. Matsuoka-Uno et al [4] showed that the mineralization of organic matter in humus-rich Andosol is greatly enhanced by liming and phosphorus fertilization, shedding light on the importance of fertilizer management for C accumulation in agricultural land, similar to the study by Liu et al [3].…”
mentioning
confidence: 61%